حال الراوي عبد الله بن لهيعة جرحًا وتعديلا وتحقيق أمر اختلاطه: The Status of the Narrator Abdullah ibn Luhaīyʿah: Criticism (Jarḥ), Commendation (Ta‘dil), and the Investigation of Confusion (Ikhtilat) - فراز الحق بن نجم الحق (الدراسات الإسلامية, 2023)
This article examines the contentious status of Abdullah ibn Luhaīyʿah as a Ḥadīth narrator, focusing on the divergent perspectives within Ḥadīth scholarship. Despite his significance as a source for legal rulings and jurisprudential deductions, opinions on his reliability vary widely among scholars. Recognising the existing debates and uncertainties, this research aims to provide a comprehensive analysis of the assessments made by Muḥaddiṯhīn regarding ibn Luhaīyʿah. The research systematically applies the review and criticism process of the jaraḥ and taʿdīl literature by charting the range of scholarly opinions on his trustworthiness and potential weaknesses, while critically evaluating the arguments presented, and clarifying the implications of these assessments for accepting his narrations. This article addresses a gap in dedicated research on ibn Luhaīyʿah, contributing to a more nuanced understanding of his position within Ḥadīth studies and offering valuable insights for navigating the complexities of Ḥadīth transmission.